DNA barcoding of a tropical anguillid eel, Anguilla bicolor (Actinopterygii: Anguilliformes), in Indo-Pacific region and notes on its population structure - Norarfan, Ahmad Fathi; Azreena Mokti, Siti Shazwani; Taha, Hussein; Amin, Muhamad; Ali, Muhamad; Arai, Takaomi (Zoologia, 2021)
The tropical anguillid eel, Anguilla bicolor McCelland, 1844, includes two subspecies, Anguilla bicolor bicolor McCelland, 1844 and Anguilla bicolor pacifica Schmidt, 1928, and is distributed across the Indo-Pacific region. Although A. bicolor is widely distributed and recognized as an important fish resource in the Indo-Pacific region, few studies have been conducted on its genetic variation and population structure. DNA barcoding of A. bicolor specimens collected in the Indo-Pacific region was carried out in this study using mitochondrial cytochrome c oxidase subunit I. Anguilla bicolor was found to diverge genetically, which supported its classification into two different subspecies. In addition, our study showed that A. bicolor bicolor had two genetically distinct populations/groups, and these different populations co-occur geographically in Indonesia and Malaysia in the eastern Indian Ocean. Our findings suggest that the eel larvae might be transported from at least two geographically different spawning grounds in the Indian Ocean, and then recruited to and settled in the same habitats in Indonesian and Malaysian waters. The molecular evidence calls for further research on the life history, stock assessment and protection of the populations of A. bicolor bicolor in Indonesia and Malaysia.